YOSHLARNING JISMONIY SIFATLARINI RIVOJLANTIRISHDA TA’LIM-TARBIYA TAMOYILLARI - Qaljanov, P. (SCIENCE and SOCIETY, 2024)
The principles of physical education provide an approach to the development of a person as a perfect individual in all respects, which contributes to the development of children’s physical abilities, motor skills and skills in combination with the implementation of individual child education and comprehensive education.